Observer‐based finite‐time output‐feedback controller for DC‐DC buck converters with unknown load variations. (24th July 2019) - Cheng, Yingying; Jin, Qingchun; Du, Haibo; Xu, Yeyuan; Zhu, Wenwu; Jiang, Congrang
Summary: The output voltage regulation problem of a DC‐DC buck converter is investigated in this paper via an observer‐based finite‐time output‐feedback control approach. Considering the effects of unknown load variations and the case without current sensor, by using the technique of adding a power integrator and the idea of nonseparation principle, a finite‐time voltage regulation control algorithm via dynamic output feedback is designed. The main feature of the designed observer and controller does not need any load's information. Theoretically, it is proven that the output voltage can reach the desired voltage in a finite time under the proposed controller. The effectiveness of the proposed control method is illustrated by numerical simulations and experimental results.